Catalogo de germoplasma de: Phaseolus coccineus L. Phaseolus polyanthus Green - Schmit, V. (International Center for Tropical Agriculture, 1988)
Among the network of International Research Centers, CIAT is responsible for collecting and preserving the world's bean germplasm of the genus Phaseolus (P. vulgaris, P. acutifolius, P. lunatus, P. coccineus, and P. polyanthus). The catalog includes 785 new accessions of P. coccineus, P. polyanthus, and related species that have multiplied in CIAT. Due to the allogamous character of the species, a methodology was established that allows for preserving the variability within each accession, and at the same time, prevents contamination with other accessions. Multiplication is achieved in mesh houses in Popayan, and in the field, with racemes protected by paper bags, in Rionegro. In both cases, polinization is manual, which in turn prevents obtaining a great no. of seeds/plant. The catalog is divided into 3 main sections: (a) a brief description of the collection, (b) descriptors (according to the list published by the International Board for Plant Genetic Resources with some modifications), and (c) data on passport, collection, caracterization, and evaluation. (CIAT)